Fatigue in additive manufactured metals - Berto, Filippo; Du Plessis, Anton (Additive Manufacturing Materials and Technologies Series, 2023)
Fatigue in Additive Manufactured Metals provides a brief overview of the fundamental mechanics involved in metal fatigue and fracture, assesses the unique properties of additive manufactured metals, and provides an in-depth exploration of how and why fatigue occurs in additive manufactured metals. Additional sections cover solutions for preventing it, best-practice design methods, and more. The book recommends cutting-edge evidence-based approaches for designing longer lasting additive manufactured metals, discusses the latest trends in the field and the various aspects of low cycle fatigue, and looks at both post-treatment and manufacturing process-based solutions. By providing international standards and testing procedures of additive manufactured metal parts and discussing the environmental impacts of additive manufacturing of metals and outlining simulation and modeling scenarios, this book is an ideal resource for users in industry.